Walking environments for aging communities in municipality regions in China: measuring physical function toward population health challenges - Wei, Song; Yu, Hongli; Sun, Chen (Frontiers in Public Health, 2025)
Accessibility to public facilities and walking distance to destinations contribute significantly to mobility and cognitive function in aging communities. However, research on gender variation across these attributes remains unclear in Chinese megacities. This study examines the relationship between environmental characteristics and physical performance measures in aging communities in Chongqing municipality, China. It also assesses potential improvements in walkability-related health outcomes. Researchers collected cross-sectional data consisting of 346 samples representing 197 women and 149 men spanning 60–85 years in 2023. Physical performance was assessed using hand-grip strength, maximum gait speed, timed up-and-go tests, and one-legged stance assessments using multilinear regression tests. Walkability indicators were analyzed in relation to these outcomes to determine walkability effects. Gender-specific correlations were explored through comparative analysis. Results indicated that intersection density and availability of destinations were significantly associated with body balance and performance (one-legged stance) in both genders. In men, population density and access to public transportation were associated with hand-grip strength, whereas women exhibited stronger relationships between walkability and mobility (gait speed and timed up-and-go performance). The Walk Score significantly improved body balance and strength in women, while men experienced substantial gains in physical stability from population density and destination accessibility. These findings emphasize the importance of walkable environments in enhancing physical performance in older adults, revealing gender-specific variations in walkability attributes. Results indicate that walkability infrastructure can promote mobility independence. Future research may examine longitudinal impacts and practical measures for population health challenges.